Electrospinning Method Used to Create Functional Nanocomposites Films 2018
DOI: 10.5772/intechopen.76068
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofibers for Entrapment of Biomolecules

Abstract: This chapter focuses on nanofiber fabrication by electrospinning techniques for the effective immobilization of biomolecules (such as enzymes or active pharmaceutical ingredients-APIs). In this chapter, the development of precursor materials (from commercial polymer systems to systematically designed biopolymers), entrapment protocols, and precursor-nanofiber characterization methods are represented. The entrapment ability of poly(vinyl alcohol) and systematically modified polyaspartamide nanofibers was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Furthermore, based on the high surface area, high permeability, cost effectiveness and the large availability of appropriate polymers allowing a tunable nanofiber surface morphology, this method gains more and more attention in both, academic and industrial sectors. 68 The optimal enzyme loading through entrapment is the lowest amount of the enzyme assuring the highest biocatalytic activity. 69 According to the literature, the most used protocol for enzyme entrapment in polymeric nanofibers based on PVA and chitosan (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, based on the high surface area, high permeability, cost effectiveness and the large availability of appropriate polymers allowing a tunable nanofiber surface morphology, this method gains more and more attention in both, academic and industrial sectors. 68 The optimal enzyme loading through entrapment is the lowest amount of the enzyme assuring the highest biocatalytic activity. 69 According to the literature, the most used protocol for enzyme entrapment in polymeric nanofibers based on PVA and chitosan (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The polar solvents influenced the properties of PVA through stereoregularity, which was already influenced by the dipole–dipole interactions or hydrogen bonds with other polar groups. 68 Based on these experimental facts, n -hexane was chosen as the solvent since after keeping under stirring at 50 °C and 1000 rpm for 24 hours, only a loss of 0.46% was recorded, as compared with chloroform (of 1.47%), THF (2.77%) or DCM (8.1%), demonstrating the impressive biocatalyst stability in organic media.…”
Section: Resultsmentioning
confidence: 99%
“…Electrostatic fiber formation (electrospinning) is an easy-to-perform, fast, scalable, low-excipient process with the ability to turn enzymes into a solid formula that is easy to handle, to store, and to distribute into defined doses in drugs. Our previous studies showed that poly(vinyl alcohol) nanofibers were well applicable for lipase immobilization [ 46 , 49 , 50 , 51 ]. The specific enzyme activity of entrapped lipases could be increased due to the improved dispersion of enzyme molecules within the nanofibers with high specific surface area.…”
Section: Resultsmentioning
confidence: 99%
“…The specific enzyme activity of entrapped lipases could be increased due to the improved dispersion of enzyme molecules within the nanofibers with high specific surface area. Moreover, some substrate-like additives could further improve the activity of the lipases [ 46 , 49 , 50 , 51 ]. To study the solid formulation of lipase–CD pairs selected from the previous electrospinning experiments, we performed the nanofiber formation as described earlier (see Section 2.6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Its application allows for the creation of solid fibrous polymer structures with exceptionally high specific surfaces with a submicron diameter [41]. These structures could immobilize biological agents to create unique medicine formulations, create filtration-ready synthetic membrane structures, and even create fabrics for apparel [42][43][44]. Electrostatic repulsion takes place between the identically charged polymer particles and elongates the polymer solution droplet when electric potential in the range of kilovolts is applied to the solution emitter.…”
Section: Introductionmentioning
confidence: 99%